2021
DOI: 10.17219/acem/131750
|View full text |Cite
|
Sign up to set email alerts
|

Pack-year cigarette smoking affects the course of palmoplantar pustulosis

Abstract: Background. Palmoplantar pustulosis (PPP) is a chronic inflammatory disease with poorly understood pathogenesis. The disease has a chronic course with improvements and exacerbations. Due to palmoplantar location, PPP has a severely negative impact on patients' quality of life.Objectives. To identify demographic and environmental factors, concomitant diseases, medications, and bacterial factors which may affect the course of PPP. Materials and methods.A total of 51 patients suffering from PPP took part in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The duration and amount of smoking influence the risk and disease severity. 7 , 16 , 101 , 103 Quitting smoking leads to a clinical improvement of PPP (p=0.007) and improves treatment efficacy. 9 , 104 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The duration and amount of smoking influence the risk and disease severity. 7 , 16 , 101 , 103 Quitting smoking leads to a clinical improvement of PPP (p=0.007) and improves treatment efficacy. 9 , 104 …”
Section: Discussionmentioning
confidence: 99%
“…These include increased IgA antibodies against gliadin, moderate to severe anxiety (p<0.001), dysbiosis of the oral biota, infections of the oral cavity (mainly the tonsils), thyroid disease, metabolic syndrome, arthritis (such as pustulotic arthro-osteitis or psoriatic arthritis), and PV. 18,84,[92][93][94][95][96][97][98][99][100][101] PPP has also been identified as a predictor for the development of psoriatic arthritis in patients with psoriasis. 102 However, some authors separate palmoplantar pustular psoriasis from palmoplantar pustulosis in cases of psoriatic features such as plaques, generalized pustules, psoriatic arthritis, or a positive family history of psoriasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the analysis, the smoker group was further divided into two groups based on the „pack-year”, defined as (packs smoked per day) × (years as a smoker). This value is widely used as a measure of cumulative cigarette intake 24 . For this purpose, the obtained median value of the pack-year among the smokers was used as a basis for dividing the group.…”
Section: Methodsmentioning
confidence: 99%
“…Third, we know that smoking affects PPP. In a 51-patient study reported by Putra-Szczepaniak et al, the severity of PPP was higher in patients who were addicted to smoking and who smoked pack-years [ 6 ]. Thus, it is known that smoking is a factor that can influence the efficacy of the drug, but Burden et al [ 1 ] did not specify the smoking status of the patients.…”
Section: Dear Editormentioning
confidence: 99%